Carbamoylimines of Methyltrifluoropyruvate in the Diels-Alder’s Azareaction with Cyclopentadiene - Aksinenko, A.Yu.; Kalashnikova, I.P.; Sokolov, V.B. (Biomedical Chemistry: Research and Methods, 2018)
Carbamoylimines of methyl trifluoropyruvate react with cyclopentadiene with to formation of trifluoromethyl-containing azabicyclo [2.2.1] heptenes and tetrahydrocyclopenta[e][1,3]oxazines. NMR experiments involving DEPT and 1H{19F} determined the structure of the synthesized heterocycles and assignment of the signals in NMR spectra and established the exo-position of the CF3-group in azabicyclo[2.2.1]heptenes.